Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/diagnostics12112793
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-like Cells Are Increased in Patients with Vision-Threatening Diabetic Retinopathy and Correlate with Macular Edema

Abstract: Macrophage-like cells (MLCs) are potential inflammatory biomarkers. We previously showed that MLCs are increased in proliferative diabetic retinopathy (PDR) eyes. Vision-threatening diabetic retinopathy (VTDR) includes PDR, severe non-PDR (NPDR), and diabetic macular edema (DME). No prior data exist on MLCs in eyes with severe NPDR or DME. This prospective, cross-sectional optical coherence tomography-angiography (OCT-A) imaging study included 40 eyes of 37 participants who had NPDR classified as non-VTDR (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…19 Over the last 2 years, there has been a growing interest in utilizing OCTA and SS-OCT for the visualization of retinal microglia, which appear as hyperreflective bodies that the existing literature identifies as macrophage-like cells. [20][21][22][23][24] However, the term "macrophage" implies cells of myeloid origin. Many tissues, including retina and brain, have immune cells of both yolk sac and myeloid origin.…”
Section: Discussionmentioning
confidence: 99%
“…19 Over the last 2 years, there has been a growing interest in utilizing OCTA and SS-OCT for the visualization of retinal microglia, which appear as hyperreflective bodies that the existing literature identifies as macrophage-like cells. [20][21][22][23][24] However, the term "macrophage" implies cells of myeloid origin. Many tissues, including retina and brain, have immune cells of both yolk sac and myeloid origin.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have used OCT to visualize in vivo macrophage-like cells (MLCs), which is thought to be microglia or hyalocytes, located at the vitreoretinal interface. OCT found MLC showed increased density, nonuniform distribution and altered morphology in eyes of patients with proliferative diabetic retinopathy (PDR) (Corsi and Zhang and Nesper. 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, activated microglia are tightly associated with blood vessels that are closely connected geographically and promote microangiopathy in DR. Microglia/macrophages accumulate in the retina under the prolonged effects of hyperglycemia, indicating their contribution to the development of the disease. Optical coherence tomography angiography revealed that patients with PDR had significantly more macrophage-like cells surrounding their retinal vessels than healthy individuals, diabetics without DR, and patients with NPDR ( 96 ); diabetic macular edema was the most relevant factor contributing to the increase in macrophage-like cells ( 97 ). Moreover, macrophages near the vitreoretinal interface, mainly microglia, may act as biomarkers for inflammation ( 98 ).…”
Section: Macrophage/microglia Polarization In Drmentioning
confidence: 99%